A neural network approach to predicting the quality indicators of the purification department of a sugar factory - Zaiets, N.; Lutska, N.; Vlasenko, L. (Energy and Automation, 2024)
The article proposes a model of the defecosaturation department of a sugar beet processing plant based on a neural network, which predicts the main indicators of the efficiency of diffusion juice purification. The predictive model allows you to adjust the operation mode of the department by analyzing the unmeasured qualitative indicator of the purification effect. The developed model also predicts the color of the semi-finished product, as well as the loss of sugar in the filter cake I and II saturation with an error of less than 5%. Unlike existing solutions, forecasting is performed in real time using a set of indicators of an automation system and an industrial laboratory. A predictive neural network model is an MLP universal for approximating non-linear complex functions with many variables. The model has 32 inputs, 4 outputs and one hidden layer with 23 neurons. The main technological variables from the automation system – temperatures, flow rates, pressure, pH in the apparatus, as well as from the industrial laboratory – alkalinity, SO content in the saturation gas will be fed into the network input. This allows to increase the informative support of the operator-technologist regarding the quality indicators of the enterprise without additional load on the industrial laboratory and without additional cost automatic quality devices.Key words: defecosaturation department, neural network, forecast, sugar beet, quality assessment